2007
DOI: 10.1597/06-220.1
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Imaging of the Levator Veli Palatini Muscle in Speakers with Repaired Cleft Palate

Abstract: This study contributes to a better understanding of cleft palate anatomy in comparison with normal anatomy of the levator veli palatini muscle. The use of MRI shows promise as an important tool in the diagnosis and eventual aid to treatment decisions for individuals born with cleft palate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

10
87
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(99 citation statements)
references
References 26 publications
10
87
2
Order By: Relevance
“…The levator muscle was found to be shorter and thinner (mean length of 40 mm and mean thickness of 3.7 mm) compared with the normative measures reported by Ettema et al 5 The angles of origin were more variable (ranging from right = 50-Y69-and left = 60-Y72-) across patients compared with the reported normative measures. The results of the study of Ha et al 6 serve as preliminary data in investigating the possible differences in the levator muscle in individuals with cleft palate compared with individuals without a cleft palate.…”
mentioning
confidence: 99%
“…The levator muscle was found to be shorter and thinner (mean length of 40 mm and mean thickness of 3.7 mm) compared with the normative measures reported by Ettema et al 5 The angles of origin were more variable (ranging from right = 50-Y69-and left = 60-Y72-) across patients compared with the reported normative measures. The results of the study of Ha et al 6 serve as preliminary data in investigating the possible differences in the levator muscle in individuals with cleft palate compared with individuals without a cleft palate.…”
mentioning
confidence: 99%
“…Ha et al (2007) reported that participants with residual hypernasality demonstrated levator muscle dimensions that were different from levator muscle features in adults without cleft palate. Perry, Kuehn, Sutton, Gamage, and Fang (2014) hypothesized that velopharyngeal structures vary on the basis of sex and race among the adult population with normal anatomy.…”
mentioning
confidence: 99%
“…Studies have demonstrated the use of MRI in assessing levator muscle characteristics in adults with normal velopharyngeal anatomy (Bae, Kuehn, Sutton, Conway, & Perry, 2011;Ettema et al, 2002;Perry, Kuehn, & Sutton, 2013) as well as in adults with repaired cleft palate and hypernasal speech (Ha, Kuehn, Cohen, & Alperin, 2007). Ha et al (2007) reported that participants with residual hypernasality demonstrated levator muscle dimensions that were different from levator muscle features in adults without cleft palate.…”
mentioning
confidence: 99%
“…Models can integrate the wealth of literature describing the anatomy, physical properties, and in vivo function of the VP mechanism [15][16][17][18][19][20][21][22][23][24][25] and then be used to systematically investigate cause-and-effect relationships that would be either impossible to accomplish in vivo or take decades of clinical trials to uncover. For example, models have the ability to quantify the effect of varying surgical parameters, like the extent of LVP overlap.…”
mentioning
confidence: 99%